Gender Discrimination In The Drama Series At-Tabadul (The Exchange) A Semiotics Roland Barthes - Malika Kautsar Ilmi; Nurlinah Nurlinah; Khomisah Khomisah (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study was motivated by the portrayal of gender discrimination against women in the film The Exchange. The study aims to describe the forms of gender discrimination and to uncover the meanings behind these representations. The method used is qualitative descriptive analysis based on Roland Barthes’s theory of semiotics, which includes an analysis of denotation, connotation, and myth. The research data consist of scenes, dialogues, and visual elements that illustrate practices of gender discrimination in the film The Exchange. Data collection was conducted through screenshots and notes on scenes relevant to the research focus. The results show that gender discrimination is represented through various forms of injustice experienced by female characters, both within the family and in the workplace. These forms of discrimination include the disregard for women’s abilities, unequal treatment, negative stereotypes, restrictions on social roles, and a lack of recognition of women’s rights and needs. This study also found that gender discrimination is not only perpetrated by male characters but is also reproduced by female characters who have internalized patriarchal values. Through these portrayals, the film The Exchange illustrates the consequences or impacts of discrimination that can affect gender relations and diminish women’s status in social life.